Effects of Quorum Sensing Systems on Regulatory T Cells in Catheter-Related Pseudomonas aeruginosa Biofilm Infection Rat Models - Lei Feng; Qingqing Xiang; Qing Ai; Zhengli Wang; Yunhui Zhang; Qi Lu (Mediators of Inflammation)
Background. Quorum sensing (QS) systems play an important role in modulating biofilm formation. Recent studies have found that the QS molecules had complex effects on the host immune systems. In addition, regulatory T cells (Tregs), known as important negative regulators in the immune system, have been found upregulated in multiple chronic infections. Therefore, the QS systems were hypothesized to be involved in modulating Tregs in biofilm-associated infections. Object. To explore the effects of QS systems on Tregs in catheter-related Pseudomonas aeruginosa biofilm infection rat models. Method. Catheter-related Pseudomonas aeruginosa biofilm infection rat models were established; the bacterial clearance rates, total cell counts in bronchoalveolar lavage (BAL) fluid, pathological changes of lungs, and the levels of Foxp3, TGF-β1, and IL-10 in PAO1 strain group were examined and compared with the QS-mutant ΔlasRΔrhlR and ΔlasIΔrhlI groups. Results. In PAO1 group, the bacterial clearance rates were lower, total cell counts were higher, pathological changes were severer, and the levels of Foxp3, TGF-β1, and IL-10 were significantly higher compared with QS-mutant groups (p<0.05). No significant difference was observed between the two QS-mutant groups (p>0.05). Conclusion. QS systems can trigger host immune system, accompanied with the upregulation of Tregs.